Cymatodera bicolor Say 1825 ... - Majka, Christopher G. (Zenodo, 2006)
Cymatodera bicolor (Say, 1825) NOVA SCOTIA: Kings Co.: Kentville, 10.vii.1948, CNC. Only one specimen of this species has been collected in the Maritime Provinces (Figure 5). Further research is required to determine if this specimen represents an isolated population in the Annapolis Valley of Nova Scotia (a relatively warmer portion of the province) or if this individual was a wind-blown stray. Cymatodera bicolor is known from Maine (Chandler 2001). Cymatodera favours immature stages of prey such as larvae of cynipoid wasps and other larvae associated with galls, fruit tree caterpillars, and larvae of bark beetles, cerambycids, and buprestids (Opitz 2002). Regional Distribution: CT, Connecticut; MA, Massachusetts; ME, Maine; NB, New Brunswick; NF, Newfoundland; NH, New Hampshire; NS, Nova Scotia; NY, New York; ON, Ontario; QC, Québec; PE, Prince Edward Island; RI, Rhode Island; VT, Vermont. Continental Distribution: 1, Northeastern; 2, Southeastern; 3, Southwestern; 4, Northwestern; 5, Central. Regional ... : Published as part of Majka, Christopher G., 2006, The checkered beetles (Coleoptera: Cleridae) of the Maritime Provinces of Canada, pp. 31-46 in Zootaxa 1385 on pages 33-34, DOI: 10.5281/zenodo.175098 ...